Sexueller Missbrauch Minderjähriger durch katholische Geistliche in Deutschland - Hellmann, Deborah F.; Fernau, Sandra (Nomos Verlagsgesellschaft mbH & Co. KG, 2014)
"In this anthology, empirical findings on sexual abuse by Catholic clerics in Germany are presented for the first time. The results are based on data of two samples of victims and thereby provide in-depth knowledge about background, characteristics and consequences of sexual abuse within the Catholic Church: a quantitative questionnaire study and a qualitative interview study. The analyses of the quantitative survey emphasize the central characteristics of the abuse and their psychosocial effects on the victims. Additionally, reactions of the public authorities and the Catholic Church regarding the victims disclosure of the sexual abuse are taken into account. The qualitative research focusses on victims different biographical ways of handling the sexual abuse. Particularly the recourse to Catholic beliefs in dealing with the experienced sexual violence is revealed."
German
Keywords: Kriminologie: Rechtliche Aspekte; Strafrecht; Kriminologie; Strafvollzug